The contemporary social theory and the emergency of the "sociology of the childhood" in the 2nd modernity: some theoretical-political aspects - Rita de Cássia Marchi (Universidade Federal de Santa Catarina, 2005)
Rehearsal divided in 2 parts: in the first part if it discusses the recent emergency of the Sociology of the Childhood in your relationships with the General Sociology and, on Monday, the childhood as a subject essentially politics.